Government House, Trinidad - (:unkn) unknown (G.G. Belgrave, Trinidad, 2009)
A picture of a walkway leading to the Governor's House main building starting at a fountain, tropical plants of the Botanical Gardens line the walkway and at the back of the building are the St. Ann's Hills. The postcard is addressed to Mrs. Mary Sewnenig, Coatesville, PA, U.S.A. Affixed to the postcard is a US 1 cent stamp, postmarked December 12, 1910.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Fountains--Trinidad and Tobago; 1910; President's House, The